ANALISIS TEKANAN STATIK ALIRAN DI PERMUKAAN PITOT STATIK TEROWONGAN ANGIN TRANSONIK LAPAN - Ariwibowo, Agus; Fitroh, Ahmad Jamaludin; Herdiana, Dana (BRIN Publishing, 2007)
Static pressure stream analysis has been done on the surface of pitot static for LAPAN transonic wind tunnel by means of numeric and analytic methods. Static pressure hole is placed at 25 cm behind static pitot leading edge. Numerical analysis result demonstrates that shock wave begins to rise under free stream with velocity of 0.9 march. Shock wave occurs in an area around static pitot leading edge so the stream velocity around static pressure hole almost equal with free stream velocity. There is shock wave that cause decreasing of stream total pressure. By known the total pressure and streamn velocity around static pressure hole then static pressure can be calculated. Mach number in the test section can be known from pressure ratio. Keywords: Static pitot, Shock wave, Static pressure, Transonic.